An Exploration of Taiwanese Customers’ Purchase Intention of Organic Food using the Theory of Planned Behaviour - Wang, Kimberly (2017)
The organic food industry is one of the fastest growing food sectors in Taiwan. Following a number of food scandals, customers are more concerned than ever about healthy food selection. Organic food is regarded as a healthy, environmentally friendly and safe option. However, regarding previous negative news following government food safety inspections, customers are beginning to doubt the reliability of the certification system and labelling. Therefore, to understand customers’ perceptions of organic foods and their level of trust in government and producers, this study examines how attitude, subjective norms, perceived behavioural control (PBC), producer’s trust, and institutional trust positively influence customers’ organic foods purchase intentions. Moreover, the research also explores the influence of the two trust constructs on purchase intention. This research uses the online questionnaire as the main methodology. The main findings are concluded as follow. First, although organic food is perceived as bringing benefits to person and society, its high price is still regarded as the main purchase barrier to most of the respondents. Second, the subjective norm plays one of the main roles in driving respondents’ purchase intention. Third, it is apparent that participants trust the producer more than they trust the governmental bodies. Moreover, among the various certification bodies, certification by a university is the most credible to respondents. The findings support that attitude, subjective norm, and trust in producer trust can explain the Taiwanese respondents’ organic food purchase intentions, while the PBC and institutional trust have no significant influence. In terms of study limitations, the small sample and analysis method are the two main constraints. In addition, another factor affecting the research results is that there is the only one dimension applied in the PBC construct to examine the whole PBC. Therefore, further research can focus on improving sampling, questionnaire design, and analysis method.